Visualization of the Long Thoracic Nerve using High-Resolution Sonography - Lieba-Samal, D.; Morgenbesser, J.; Moritz, T.; Gruber, G. M.; Bernathova, M.; Michaud, J.; Bodner, G. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: The long thoracic nerve (LTN) innervates the serratus anterior muscle (SA) which plays an important role in shoulder function. Evaluation of the LTN has so far been restricted to clinical assessment and partly electromyography and neurography. Progress of high-resolution ultrasound (HRUS) increasingly enables visualization of small peripheral nerves and their pathologies. We therefore aimed at (a) clarifying the possibility of visualization of the LTN from its origin to the most distal point in the supraclavicular region visible and (b) developing an ultrasound protocol for routine use. We further present two cases of patients with LTN pathology.Methods: The study consisted of two parts: Part 1 included 4 non-enbalmed human bodies in whom the LTN (n = 8) was located and then marked by ink injection. Correct identification was confirmed by anatomical dissection. Part 2 included 20 healthy volunteers whose LTN (n = 40) was assessed independently by two radiologists. Identification of the LTN was defined as consensus in recorded images.Results: LTN was clearly visible in all anatomical specimens and volunteers using HRUS and could be followed until the second slip of the serratus anterior muscle from the supraclavicular region. In anatomical specimens, dissection confirmed HRUS findings. For all volunteers, consensus was obtained. The mean nerve diameter was 1.6 mm ± 0.3 (range 1.1 – 2.1 mm) after the formation of the main trunk.Discussion: We hereby confirm a reliable possibility of visualization of the LTN in anatomical specimens as well as in volunteers. We encourage HRUS of the LTN to be part of the diagnostic work-up in patients presenting with scapular winging, shoulder weakness or pain of unknown origin.
Keywords: normal variants; long thoracic nerve; scapula alata; shoulder pain